Epidemiological investigation of an Acinetobacter baumannii outbreak using core genome multilocus sequence typing. (June 2019) - Venditti, Carolina; Vulcano, Antonella; D'Arezzo, Silvia; Gruber, Cesare Ernesto Maria; Selleri, Marina; Antonini, Mario; Lanini, Simone; Marani, Alessandra; Puro, Vincenzo; Nisii, Carla; Di Caro, Antonino
Highlights: Thirteen carbapenem-resistant Acinetobacter baumannii strains from an Italian ICU were investigated. Traditional typing methods highlighted one cluster, whereas cgMLST showed two different clusters. cgMLST highlighted two transmission events, supported by epidemiological data. WGS-based cgMLST is a valuable tool, better suited for prompt epidemiological investigations. Abstract: Objectives: Carbapenem-resistant Acinetobacter baumannii (CRAB) is a serious nosocomial pathogen that causes a variety of serious, often life-threatening, infections and outbreaks. This study aimed to investigate the molecular epidemiology of clinical CRAB isolates from an outbreak that occurred in the intensive care unit (ICU) of an Italian hospital. Methods: From December 2016 to April 2017, 13 CRAB isolates were collected from seven patients treated in the ICU at 'L. Spallanzani' Hospital (Rome, Italy). Typing was performed by repetitive extragenic palindromic PCR (rep-PCR) using a DiversiLab ® system. Whole-genome sequencing (WGS) data were used for in silico analysis of traditional multilocus sequence typing (MLST) results, to identify resistance genes and for core genome MLST (cgMLST) analysis. Epidemiological data were obtained from hospital records. Results: All isolates showed a carbapenem-resistant profile and carried the bla OXA-23 carbapenemase gene. Typing performed by rep-PCR and MLST showed that the isolates clustered into one group, whilst the cgMLST approach, which uses 2390 gene targets to characterise the gene-by-gene allelic profile, highlighted the presence of two cluster types. These results allowed us to identify two patients who were likely to be the source of two separate transmission chains. Conclusion: These results show that WGS by cgMLST is a valuable tool, better suited for prompt epidemiological investigations than traditional typing methods because of its higher discriminatory ability in determining clonal relatedness.